Polymer-Based Materials Loaded with Curcumin for Wound Healing Applications - Alven, Sibusiso (Polymers (Basel), 2020)
Some of the currently used wound dressings have interesting features such as excellent porosity, good water-absorbing capacity, moderate water vapor transmission rate, high drug loading efficiency, and good capability to provide a moist environment, but they are limited in terms of antimicrobial properties. Their inability to protect the wound from microbial invasion results in wound exposure to microbial infections, resulting in a delayed wound healing process. Furthermore, some wound dressings are loaded with synthetic antibiotics that can cause adverse side effects on the patients. Natural-based compounds exhibit unique features such as good biocompatibility, reduced toxicity, etc. Curcumin, one such natural-based compound, has demonstrated several biological activities such as anticancer, antibacterial and antioxidant properties. Its good antibacterial and antioxidant activity make it beneficial for the treatment of wounds. Several researchers have developed different types of polymer-based wound dressings which were loaded with curcumin. These wound dressings displayed excellent features such as good biocompatibility, induction of skin regeneration, accelerated wound healing processes and excellent antioxidant and antibacterial activity. This review will be focused on the in vitro and in vivo therapeutic outcomes of wound dressings loaded with curcumin.